Double insertion of transposable elements provides a substrate for the evolution of satellite DNA - McGurk, Michael P.; Barbash, Daniel A.

(untitled) (Genome Research, 2018)
Eukaryotic genomes are replete with repeated sequences in the form of transposable elements (TEs) dispersed across the genome or as satellite arrays, large stretches of tandemly repeated sequences. Many satellites clearly originated as TEs, but it is unclear how mobile genetic parasites can transform into megabase-sized tandem arrays. Comprehensive population genomic sampling is needed to determine the frequency and generative mechanisms of tandem TEs, at all stages from their initial formation to their subsequent expansion and maintenance as satellites. The best available population resources, short-read DNA sequences, are often considered to be of limited utility for analyzing repetitive DNA due to the challenge of mapping individual repeats to unique genomic locations. Here we develop a new pipeline called ConTExt that demonstrates that paired-end Illumina data can be successfully leveraged to identify a wide range of structural variation within repetitive sequence, including tandem elements. By analyzing 85 genomes from five populations of Drosophila melanogaster, we discover that TEs commonly form tandem dimers. Our results further suggest that insertion site preference is the major mechanism by which dimers arise and that, consequently, dimers form rapidly during periods of active transposition. This abundance of TE dimers has the potential to provide source material for future expansion into satellite arrays, and we discover one such copy number expansion of the DNA transposon hobo to approximately 16 tandem copies in a single line. The very process that defines TEs—transposition—thus regularly generates sequences from which new satellites can arise.